Bufei Decoction Alleviated Bleomycin-Induced Idiopathic Pulmonary Fibrosis in Mice by Anti-Inflammation. (8th September 2020) - Yang, Shanjun; Cui, Wenwen; Wang, Mingye; Xing, Luming; Wang, Yue; Zhu, Pengyu; Qu, Qisheng; Tang, Qiang
Abstract : Objective . This study aimed to investigate the mechanistic action and therapeutic effects of Bufei decoction on idiopathic pulmonary fibrosis (IPF) after inhalation of bleomycin. Methods . Pulmonary fibrosis model in mice was prepared by atomization inhalation of bleomycin. Then, the mice were randomly divided into five groups (control group, model group, positive group, and treatment group) and administrated the drugs for 4 weeks. H&E and Masson's staining of lung tissues were used to observe the morphological changes and deposition of fibers, and the degree of fibrosis was evaluated by hydroxyproline content. The expression and activation of NF- κ B were determined by western blotting and immunohistochemistry. The infiltration of macrophages was detected by immunostaining of CD45 and F4/80 in lung tissues. Results . In mouse IPF, Bufei decoction alleviated the pathological changes and the deposition of fibrosis by decreasing the content of hydroxyproline of lung tissues. The antipulmonary fibrosis might rely on the effects of preventing the infiltration of inflammatory cells and inhibiting the expression and activation of NF- κ B in lung tissue. Conclusion . Bufei decoction improved the process of pulmonary fibrosis by regulating the activation and expression of the NF- κ B signal transduction pathway, which provided a therapeutic option for IPF patients.